Mechanical Short-Circuit Effects of Single Core Cables - Hosemann, Gerhard; Rüger, Wolfgang (Wire, 1991)
Plastic-insulated single-core cables may be deformed by short-circuit forces to such an extent that safe operation is not possible. This applies mainly to cables laid in trefoil formation, such as frequently occurs in industrial plants. A simple model of calculation is presented which allows a determination of the permanent plastic deformation. The accuracy of the model is sufficient for practical purposes. The model is verified by tests in a heavy current laboratory. For rating the mechanical short-circuit strength it is shown to be sufficient to adhere to a maximum permissible permanent displacement. For this calculation only one material parameter, the yield point σf of the conductor material, is necessary.
UnivIS-Import:2017-12-18:Pub.1991.tech.IE.leen.mechan